1993
DOI: 10.1590/s0034-89101993000600002
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 4 - Survey of resting adults and synanthropic behaviour in South-Eastern, Brazil

Abstract: Resting adults Culicidae were collected from January 1992 through January 1993 in several habitats of the Ribeira Valley region. The diversity of species found among them suggested that the vegetation remaining within human settlements favored the survival and the population increase of some mosquitoes. Among there are: Ae. scapularis, Ae. serratus, Cx. (Culex), Cx. nigripalpus and Cx. (Melanoconion) such as Cx. ribeirensis. That preservation role may be attributed to the rearing of livestock and the consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0
9

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 14 publications
4
35
0
9
Order By: Relevance
“…quinquefasciatus is historically considered as a typical urban mosquito (Causey et al 1945, Deane 1951, Forattini et al 1978b, 1993c. In the present study, this was the only truly eusynanthropic species found (Fig.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…quinquefasciatus is historically considered as a typical urban mosquito (Causey et al 1945, Deane 1951, Forattini et al 1978b, 1993c. In the present study, this was the only truly eusynanthropic species found (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…nigripalpus has demonstrated in other studies a more varied behavior. Lourenço-de-Oliveira (1984) collected this Culicinae in a deeply altered area in the State of Rio de Janeiro and Forattini et al (1993c) reported its preference for anthropic modified environment. Forattini et al (1995b) remarked that the behavior of Cx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main motivation for the construction of the model here presented as well as the applications made was the recent studies by Forattini et al 4 on mosquitoes at an experimental rice irrigation system 5,6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…As fêmeas são ecléticas, mas parecem preferir grandes mamíferos para o repasto sanguíneo 1,11 . São encontrados com certa abundância em ambientes silvestres primitivos e matas secundárias e apresentam pouca tendência à domiciliação 21,22 . 15,16 .…”
unclassified